The protein composition of human adenovirus replication compartments - Paloma Hidalgo; Amada Torres; Pierre M. Jean Beltran; Gamaliel López-Leal; Luca D. Bertzbach; Thomas Dobner; S. J. Flint; Ileana M. Cristea; Ramón A. González (mBio)
ABSTRACT Human adenoviruses are double-stranded DNA viruses that replicate in the cell nucleus and induce the formation of replication compartments (RCs) that are critical in viral replication and control of virus-host interactions. RCs are specialized virus-induced subnuclear microenvironments where not only viral genome replication and expression are orchestrated but also host proteins that restrict viral replication are co-opted and subverted. The protein composition of these RCs remains largely unexplored. In this study, we isolated adenovirus RC-enriched fractions from infected cells at different times post-infection and employed a tandem mass tag-based quantitative mass spectrometry approach to identify proteins associated with RCs (data available via ProteomeXchange identifier PXD051745). These findings reveal an elaborate network of host and viral proteins potentially relevant for RC formation and function. To validate the RC-protein components identified by mass spectrometry, we employed immunofluorescence and immunoblotting techniques. Proteins previously described to colocalize in RCs in infected cells were identified in the isolated subnuclear fractions. In addition, we validated newly identified proteins associated with RCs, including the high mobility group box 1 (HMGB1), the SET nuclear proto-oncogene, the structure-specific recognition protein 1 (SSRP1), the CCCTC-binding protein (CTCF), and sirtuin 6 (SIRT6). We identified HMGB1 as a protein that binds to the viral DNA binding protein (DBP). Using shRNA knockdowns and inhibitors, we demonstrated that HMGB1 acts as a proviral factor, promoting efficient viral DNA synthesis and progeny production. Our data further suggest potential candidate targets for therapeutic intervention and provide mechanistic insights into the molecular basis of virus-host interactions.IMPORTANCEHuman adenoviruses serve as models for studying respiratory viruses and have provided critical insights into viral genome replication and gene expression, as well as the control of virus-host interactions. These processes are coordinated within virus-induced subnuclear microenvironments known as RCs. We conducted quantitative proteome analyses of RC-enriched subnuclear fractions at different times post-infection with human adenovirus species C type 5, revealing a multifaceted network of proteins that participate in the regulation of gene expression, DNA damage response, RNA metabolism, innate immunity, and other cellular antiviral defense mechanisms. Furthermore, we validated the localization of several host proteins to viral RCs using immunofluorescence microscopy and immunoblotting and identified cellular HMGB1 as a proviral factor late during infection. These findings represent the first analysis of the proteomes of isolated RCs and not only enhance our understanding of nuclear organization during infection but also shed light on the complex interplay between viral and host factors within RCs.